Grain nutritional and antioxidant profiling of diverse lentil (Lens culinaris Medikus) genetic resources revealed genotypes with high nutritional value - Riaz, Fareeha; Hameed, Amjad; Asghar, Muhammad Jawad (Frontiers in Nutrition, 2024)
The lentil (Lens culinaris Medikus ssp. Culinaris) is self-pollinating, diploid (2n = 2X = 14) crop having genome size 4 Gbp. The present study was conducted to provide a database for the evaluation of lentil antioxidant capacity, nutritional quality, and biochemical attributes. For these purposes, lentil germplasm, including 100 exotic and local genotypes from different agro-climatic zones of Pakistan were collected. Significant variation (p< 0.05) was found among the genotypes under investigation using Tukey (HSD) test. Ascorbate peroxidase was highest in ALTINOPARK, i.e., (2465 Units/g s. wt.), catalase in LPP-12110 i.e. (5595 Units/g s. wt.), superoxide dismutase in LPP 12105 i.e. (296.75 Units/g s. wt.) and peroxidase in NIAB-Masoor-2002 i.e. (3170 Units/g s. wt.). Furthermore, NLM-15016 had maximum total antioxidant capacity, i.e., (15.763 mg/g s. wt.). The maximum values of total soluble sugars (83.93 mg/g. s. wt.) and non-reducing sugars (74.79 mg/g. s. wt.) were noticed in NLM-15015. Highest reducing sugars were detected in ILL-8006 (45.68 mg/g. s. wt.) ascorbic acid in LPP-12182 (706 μg/g s. wt.), total phenolic content in NLI-17003 (54600 μM/g s. wt.), and tannins in NLI-17057 (24563 µM/g s. wt.). Highest chlorophyll a (236.12 μg/g s. wt.), chlorophyll b (317 μg/g s. wt.), total chlorophyll (552.58 μg/g s. wt.) and lycopene (10.881 μg/g s. wt.) were found in NLH 12097. Maximum total carotenoids were revealed in local approved variety Markaz-2009 (17.89 μg/g s. wt.). Principal component analysis (PCA), correlation analysis (Pearson's test) and agglomerative hierarchical clustering (AHC) was performed to detect the extent of variation in genotypes. In cluster analysis, all genotypes were categorized in to three clusters.Cluster II genotypes showed remarkable divergence with cluster III. According to PCA, the contribution of PC-I regarding tested nutritional parameters towards the variability was the highest (39.75%) and indicated positive factor loading for the tested nutritional and biochemical parameters. In conclusion, genotype X-2011S and 33-34-32 can be used by food industries in making pasta, multigrain bread, and snacking foods due to its high protein content for meat alternative seekers. Identified genotypes with high nutritional attributes can be utilized to improve quality parameters in the respective lentil breeding lines.